THE NANOTECHNOLOGIES AND TRAINING OF GRADUATES OF SECONDARY SCHOOL - G.A. GALCHENKO; V.I. LOGVINOV; A.A. TIKHONOV (Advanced Engineering Research)
In the paper some aspects of training graduates of secondary schools with the purpose depositing of additions in a contents of secondary education according to development of fundamental introducings about the new phenomena, structure and properties nanomaterials are considered.